2022
DOI: 10.1055/a-1855-1839
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Herbal Medicine in the Treatment of Vitiligo: An Updated Review

Abstract: Vitiligo is a chronic disease of unknown etiology that causes progressive cutaneous depigmentation. Current pharmacological treatments have limited success and present significant risks. Many efforts have been made in recent years to explore new anti-vitiligo therapeutic strategies, including herbal-based therapies. The objective of the present review is to provide an updated overview on the most frequently used medicinal plants in the treatment of vitiligo. A bibliographical search was carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 171 publications
0
2
0
Order By: Relevance
“…Despite GBE having a wide range of pharmacological effects, its clinical application is limited and controversial [ 37 , [109] , [110] , [111] , [112] ]. The first meta-analysis confirmed the efficacy and good tolerability of GBE was patients who suffered from dementia [ 111 ], then effects on tinnitus and dizziness were demonstrated [ 113 ], but showed no prevention of acute mountain sickness [ 114 ]; subsequently, GBE in mono-therapy showed greater scientific evidence as a therapeutic option for vitiligo [ 115 ]; then, Ji HJ et al reported GBE appears to improve neurological function and dependence compared with conventional therapy for ischemic stroke at different stages, however not ameliorate in recurrence rate for ischemic stroke patients [ 11 ]; Kuo CY summarized several conflicting studies exploring the neuroprotective effect of GBE in the clinical treatment of glaucoma, drawing the conclusion that whether GBE is effective in the treatment of glaucoma further large clinical trials still need to be justified [ 116 ]; Liang N et al reported GBE could help mild cognitive impairment patients to prevent progression into dementia and to improve the ability of daily living activities [ 117 ]; Xie et al showed GBE relieves dementia symptoms in early-stage Alzheimer's disease sufferers after high doses and long-term use of GBE from clinical studies [ 118 ]. Ahmad et al summary of randomized control trials determined that the combination of GBE and pharmaceuticals has far better effects than only allopathic treatment for dementia; they also report that consider different herbal remedies in combination with FDA approved drugs are effective and more promising than monotherapy in the treatment of Alzheimer's disease [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite GBE having a wide range of pharmacological effects, its clinical application is limited and controversial [ 37 , [109] , [110] , [111] , [112] ]. The first meta-analysis confirmed the efficacy and good tolerability of GBE was patients who suffered from dementia [ 111 ], then effects on tinnitus and dizziness were demonstrated [ 113 ], but showed no prevention of acute mountain sickness [ 114 ]; subsequently, GBE in mono-therapy showed greater scientific evidence as a therapeutic option for vitiligo [ 115 ]; then, Ji HJ et al reported GBE appears to improve neurological function and dependence compared with conventional therapy for ischemic stroke at different stages, however not ameliorate in recurrence rate for ischemic stroke patients [ 11 ]; Kuo CY summarized several conflicting studies exploring the neuroprotective effect of GBE in the clinical treatment of glaucoma, drawing the conclusion that whether GBE is effective in the treatment of glaucoma further large clinical trials still need to be justified [ 116 ]; Liang N et al reported GBE could help mild cognitive impairment patients to prevent progression into dementia and to improve the ability of daily living activities [ 117 ]; Xie et al showed GBE relieves dementia symptoms in early-stage Alzheimer's disease sufferers after high doses and long-term use of GBE from clinical studies [ 118 ]. Ahmad et al summary of randomized control trials determined that the combination of GBE and pharmaceuticals has far better effects than only allopathic treatment for dementia; they also report that consider different herbal remedies in combination with FDA approved drugs are effective and more promising than monotherapy in the treatment of Alzheimer's disease [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba extract promotes repigmentation in vitiligo (Castillo et al, 2023). Carnosol from rosemary reduces inflammation markers in mice.…”
Section: Possible Side Effects Of Polyphenolsmentioning
confidence: 99%